Pendekatan Indonesia dan Amerika Serikat Terhadap Proses Demokratisasi Myanmar - Asep Setiawan; Laode Muhammad Fathun (Review of International Relations, 2023)
The paper asseses Indonesian and US approach toward Myanmar democratisation as consequences of globalisation of democracy. The US put pressure and political and economic boycott toward Myanmar to push democratisation process. In other hand, Indonesia insist that democratisation in Myanmar part of its domestic affair and no need foreign intervention. This approach is in line with basic principles of ASEAN including to build constructive engagement with Myanmar. Indonesian approach seems more suitable to create changes toward demoratisation in the Myanmar.